2009
DOI: 10.1177/159101990901500112
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of a Dural Arteriovenous Fistula Mimicking a Brain Tumor

Abstract: Dural arteriovenous fistula (d-AVF) is relatively rare. Some cases of atypical locations are often difficult to distinguish from other vascular disorders or tumors because those d-AVFs show various onsets, such as subcortical bleeding and venous infarctions. We encountered two cases of d-AVF with severe brain edema that took adequate time to distinguish from brain tumors. A 68-year-old man visited his local physician complaining of dizziness. He was diagnosed with a cerebral infarction due to the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…In our series, this was sometimes shown to be associated with enhancement and the combination of both findings could potentially mimic intra-axial neoplasms, similar to a prior case report [18]. However, similar to the observation from Kwon et al [5], these non-specific parenchymal findings were always associated with abnormally dilated and tortuous leptomeningeal and/or medullary vessels.…”
Section: Discussionsupporting
confidence: 90%
“…In our series, this was sometimes shown to be associated with enhancement and the combination of both findings could potentially mimic intra-axial neoplasms, similar to a prior case report [18]. However, similar to the observation from Kwon et al [5], these non-specific parenchymal findings were always associated with abnormally dilated and tortuous leptomeningeal and/or medullary vessels.…”
Section: Discussionsupporting
confidence: 90%
“…The natural history of DAVF is unpredictable, and due to variable clinical presentations (from asymptomatic to intracranial hemorrhage) and neuroimaging features, the diagnosis of DAVF is often delayed or missed. 1 -3 In this case, the DAVF mimicked a cerebellar tumor. Clinicians should be aware of and suspect this condition in patients with progressive focal neurological symptoms and atypical mass lesions, especially if there is a suggestion of abnormal vasculature on postcontrast images or because of the presence of flow voids.…”
Section: Case Presentationmentioning
confidence: 73%
“…A recent study 26 found a 3% recurrence rate of dAVF initially occluded by endovascular treatment, which should be kept in mind. In our review 3 cases needed retreatment for incomplete obliteration, 1 was due to persistent imaging findings 23 and 1 was due to recurrence of symptoms, 17 whereas technical difficulties caused multiple treatments in the third.…”
Section: Discussionmentioning
confidence: 84%
“…A dAVF initially misdiagnosed as a neoplastic pathology is rare, with the majority of cases accounting for brainstem lesions. Only three cases of diencephalic, [19][20][21] two cerebellar 22,23 and two supratentorial lesions 23,24 have been reported. Table 1 provides the results of our literature review.…”
Section: Discussionmentioning
confidence: 99%